Atrazine promotes breast cancer development by suppressing immune function and upregulating MMP expression - Wang, Mengqi; Chen, Junyu; Zhao, Shuhua; Zheng, Jingying; He, Kang; Liu, Wei; Zhao, Weixin; Li, Jingze; Wang, Kai; Wang, Yuru; Liu, Jian; Zhao, Lijing (Ecotoxicology and environmental safety, 2023)
There is evidence that the triazine herbicide atrazine, which is used extensively, is present in both surface water and groundwater, and its interfering effect on immune systems, endocrine systems, and tumours has been reported by laboratory and epidemiological studies. This study explored how atrazine affected 4T1 breast cancer cell development in vitro and in vivo. The obtained results showed that after exposure to atrazine, the cell proliferation and tumour volume were significantly increased and the expression of MMP2, MMP7, and MMP9 was upregulated. The thymus and spleen indices, the CD4 + and CD3 + lymphocyte percentages which from the spleen and inguinal lymph nodes, and the CD4 + /CD8 + ratio were noticeably lower than they were in the control group. Importantly, tumour-infiltrating lymphocytes such as CD4 + , CD8 + , and NK cells were decreased while Treg cells were increased. Moreover, IL-4 was increased and IFN-γ and TNF-α were decreased in the serum and tumour microenvironment. These results suggested that atrazine can suppress systemic as well as local tumour immune function and upregulate MMPs to promote breast tumour development. [Display omitted] •Atrazine promotes tumour proliferation and migration in triple-negative breast cancer.•Atrazine suppresses immune function in tumour-bearing mice.•Atrazine modulates the surrounding tumour microenvironment by suppressing anti-tumour immunity and promoting immune escape.•Atrazine exposure in 4T1 xenograft model mice is primarily toxic to immune organs.